DELIVERY BY USING THE METHODE OF WATER BIRTH - Satria Pratama, I Nyoman; Gede Budiana, I Nyoman (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Water birth is a method of pervaginam delivery where aterm pregnant women without complication soak in warm water. Nowadays, water birth has become chosen by a lot of people because of its advantages. One of the advantages of water birth delivery is decrease labor pain. There are other advantages of water birth delivery for mother and the baby. Beside those advantages, water birth also has risks and complications that need to be concerned. Water birth delivery is a safe method as long as the procedure goes well. Another thing that needs to be concerned is its policy and strategy in safety and comfort ability in using this method. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Water birth, delivery